LEXICAL AND GRAMMATICAL TRANSFORMATION IN THE PROCESS OF LITERARY TRANSLATION - Ismoilova, Gulshoda Turaboy kizi (Educational Research in Universal Sciences, 2023)
The paper deals with the study of lexico-grammatical transformations in the translation of literary text from English into Russian. Despite the large number of works covering this issue, the problem of translating literary texts is not dismissed. There is a need to systematize and study the types of lexical and grammatical transformations, used in translating literary texts, in practice. The authors of the study make an attempt of full revelation and comprehensive study of the translation transformations used to achieve the adequacy of translation to the original. In the process of work, the features of literary translation are revealed, as well as peculiarities of using transformations in literary translation; the practical expediency of using these transformations in the translation of the chosen work is determined, and the quantitative and statistical analysis of the translation transformations in the considered passages taken from the work is carried out. To solve the tasks in this paper, the following methods were used: comparative analysis of the comparison of the translation text with the text of the original work, transformational, quantitative, statistical analyses.